Methods for Isolation and Purification of Murine Liver Sinusoidal Endothelial Cells: A Systematic Review. - Jeremy Meyer; Carmen Gonelle-Gispert; Philippe Morel; Léo Bühler (PLoS ONE)
To study the biological functions of liver sinusoidal endothelial cells (LSEC) and to identify their interplay with blood or liver cells, techniques allowing for the isolation and purification of LSEC have been developed over the last decades. The objective of the present review is to summarize and to compare the efficiency of existing methods for isolating murine LSEC. Toward this end, the MEDLINE database was searched for all original articles describing LSEC isolation from rat and mouse livers. Out of the 489 publications identified, 23 reported the main steps and outcomes of the procedure and were included in our review. Here, we report and analyse the technical details of the essential steps of the techniques used for LSEC isolation. The correlations between the prevalence of some steps and the efficiency of LSEC isolation were also identified. We found that centrifugal elutriation, selective adherence and, more recently, magnetic-activated cell sorting were used for LSEC purification. Centrifugal elutriation procured high yields of pure LSEC (for rats 30-141.9 million cells for 85-98% purities; for mice 9-9.25 million cells for >95% purities), but the use of this method remained limited due to its high technical requirements. Selective adherence showed inconsistent results in terms of cell yields and purities in rats (5-100 million cells for 73.7-95% purities). In contrast, magnetic-activated cell sorting allowed for the isolation of highly pure LSEC, but overall lower cell yields were reported (for rats 10.7 million cells with 97.6% purity; for mice 0.5-9 million cells with 90-98% purities). Notably, the controversies regarding the accuracy of several phenotypic markers for LSEC should be considered and their use for both magnetic sorting and characterization remain doubtful. It appears that more effort is needed to refine and standardize the procedure for LSEC isolation, with a focus on the identification of specific antigens. Such a procedure is required to identify the molecular mechanisms regulating the function of LSEC and to improve our understanding of their role in complex cellular processes in the liver.